2020
DOI: 10.1121/10.0002641
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic features of infant-directed speech to infants with hearing loss

Abstract: This study investigated the effects of hearing loss and hearing experience on the acoustic features of infant-directed speech (IDS) to infants with hearing loss (HL) compared to controls with normal hearing (NH) matched by either chronological or hearing age (Experiment 1) and across development in infants with HL as well as the relation between IDS features and infants' developing lexical abilities (Experiment 2). Both experiments included detailed acoustic analyses of mothers' productions of the three corner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 94 publications
(173 reference statements)
0
10
0
Order By: Relevance
“…Second, hyperarticulated vowel sounds elicit more mature neural responses and more successful sound discrimination in nine-month-old infants (Peter et al, 2016) and facilitate word recognition in 19-month-olds (Song et al, 2010). Critically, these relations are observed at the level of individual mother-infant dyads: mothers who exaggerate vowels to a greater extent in their IDS have infants with more advanced speech perception skills (Kalashnikova & Carreiras, 2021;Liu, Kuhl, & Tsao, 2003) as well as larger concurrent and future vocabularies (Hartman et al, 2017;Lovcevic et al, 2020).…”
Section: Comparing Fds and Idsmentioning
confidence: 99%
“…Second, hyperarticulated vowel sounds elicit more mature neural responses and more successful sound discrimination in nine-month-old infants (Peter et al, 2016) and facilitate word recognition in 19-month-olds (Song et al, 2010). Critically, these relations are observed at the level of individual mother-infant dyads: mothers who exaggerate vowels to a greater extent in their IDS have infants with more advanced speech perception skills (Kalashnikova & Carreiras, 2021;Liu, Kuhl, & Tsao, 2003) as well as larger concurrent and future vocabularies (Hartman et al, 2017;Lovcevic et al, 2020).…”
Section: Comparing Fds and Idsmentioning
confidence: 99%
“…Although IDS is initially slow, caregivers accelerate their speech patterns across development; speech rate becomes comparable to adult-directed speech at around 2 years of infant age (Kondaurova et al, 2013; Lee et al, 2014; Narayan & McDermott, 2016; Raneri et al, 2020). In addition to adaptations of speech rate, caregivers have been found to prolong vowels in IDS (Englund & Behne, 2006; Hilton et al, 2022; Kondaurova & Bergeson, 2011; Lovcevic et al, 2020). The prolongation of vowels may ease phoneme-rate segmentation for the slow infant brain; moreover, it may help to make phonological contrasts more salient in time by slowing down the rate of phonological feature changes.…”
Section: Ids Accelerates: In Pursuit Of Electrophysiological Maturation?mentioning
confidence: 99%
“…Mothers exaggerate pitch height and pitch range to a similar degree as they do to infants with NH matched by hearing experience but not to infants with NH matched by chronological age, suggesting that the nature of IDS is a response to infants' behaviour specifically related to their hearing experience, not behaviour that is a product of more general maturational growth or cognitive development (Bergeson et al, 2006;Miyamoto et al, 2005). As for infants with hearing aids, previous studies have demonstrated that pitch height and range are exaggerated in IDS to infants with HL to a similar degree as to infants with NH (Lovcevic et al, 2020;Traci, 1998).…”
Section: Pitch Modifications In Infant-directed Speech To Infants With Hearing Lossmentioning
confidence: 92%
“…Turning to the phonetics of IDS, while vowel hyperarticulation is evident in IDS to infants with HL, the evidence indicates that (i) vowel hyperarticulation in caregivers' IDS positively correlates with infants' spoken language outcomes (Dilley et al, 2020;Hartman et al, 2017;Kalashnikova & Burnham, 2018;Lovcevic et al, 2020), and (ii) the level of vowel hyperarticulation or vowel formant exaggeration may be modulated by known contrasts in hearing status (NH versus HL, Lam & Kitamura, 2010), or by the type of hearing prosthesis, hearing aids versus cochlear implants (Wieland et al, 2015). These vowel hyperarticulation findings raise two important questions.…”
Section: Summary Of Findings and Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation